2023
DOI: 10.5603/pjnns.a2022.0079
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular non-compaction cardiomyopathy and ischaemic stroke

Abstract: This article is available in open access under Creative Common Attribution-Non-Commercial-No Derivatives 4.0 International (CC BY-NC-ND 4.0) license, allowing to download articles and share them with others as long as they credit the authors and the publisher, but without permission to change them in any way or use them commercially.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Moreover, the prefrontal and temporal white-matter networks in the motor-task state were divided into two networks in the motor state, which implied spatial reorganization in the task-related network in the motor condition. Frontotemporal regions are involved in the majority of patients with generalized epilepsy, 52,53 which might lead to a fixed and over-integrated network architecture in epilepsy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the prefrontal and temporal white-matter networks in the motor-task state were divided into two networks in the motor state, which implied spatial reorganization in the task-related network in the motor condition. Frontotemporal regions are involved in the majority of patients with generalized epilepsy, 52,53 which might lead to a fixed and over-integrated network architecture in epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the prefrontal and temporal white‐matter networks in the motor‐task state were divided into two networks in the motor state, which implied spatial reorganization in the task‐related network in the motor condition. Frontotemporal regions are involved in the majority of patients with generalized epilepsy, 52,53 which might lead to a fixed and over‐integrated network architecture in epilepsy. Here, we found that patients failed to flexibly change the network reorganization across resting and motor states, which might be related to the hyper‐integration of brain networks caused by disease 54 .…”
Section: Discussionmentioning
confidence: 99%